Rho Family GTPases - Manser, Edward J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
Humans contain more than 20 Rho type GTPases. This volume not only presents a detailed phylogenetic analysis of Rho proteins, but also discusses the possible origins of the human members. Such an analysis of human Rho GTPases has not previously been attempted. The book includes an overview of how Rho GTPases become activated which is complemented by an extensive Chapter by Darerca Owen and Helen Mott who unravel the beautiful molecular details given to us by the many structural studies of Rho GTPases. The key areas currently being investigated in relation to these ubiquitous proteins are described for both in vitro and in vivo systems. These are presented in a format that ensures the reader can approach the topic with minimal background knowledge, while ultimately bringing the subject to the level of an expert. Timely and highly authoritative, this volume illuminates newer findings, particularly as they relate to Rho proteins in vertebrate biology.
The Rho GTPases -- Evolution of the Human Rho GTPase Family -- Structural Analysis of Rho Protein Complexes -- Activation of GTPases by Dock180 Family of Proteins -- Rho GAPs — Regulators of Rho GTPases and More -- RhoA/C and the Actin Cytoskeleton -- Cdc42 and Rac Control of the Actin Cytoskeleton -- Regulation of Cell-Cell Adhesion by Rho Family GTPases -- Rho Proteins and Vesicle Trafficking -- The Prototype Rho-Associated Kinase PAK -- Genetic Analysis of Rho Protein Function in Mice -- Rho Proteins and Microtubules.
Keywords: Cell biology; Enzymology; Biochemistry; Proteomics; Cancer research; Molecular biology; Cell Biology; Enzymology; Biochemistry, general; Proteomics; Cancer Research; Molecular Medicine